Motivated by public Interest or private gain: an investigation into newspaper reportage of code of conduct tribunal trials in Nigeria (2012)
Studies have shown how political affiliation of newspapers affects coverage, of corruption trials of politicians. This study investigated the different frames in newspaper reportage of the Code of Conduct Tribunal trials of two prominent political figures in Nigeria (Bukola Saraki and Bola Tinubu). Using Framing Theory, three newspapers (The Nation, Guardian and Nigerian Tribune) were purposively selected based on national spread, sustained publication of the trials, and party-affiliation. Four hundred and eighty-four editions from 2015 to 2017 of each, totaling 1,552 were selected and content-analysed. One social commentator and one media scholar, both based in Ibadan, Oyo State were interviewed. Findings revealed that 83.1 % episodic frames focused on sensationalism and elite/party squabbles while 16.9% thematic frames were based on structural causes, and solutions to corruption. However, political-affiliation and ownership pattern determined how the corruption trials were framed. The portrayal of the two individuals was affected by the ownership pattern and political-affiliation of the newspapers. Therefore, the Nigerian Press Council (NPC) should promote ethics and social responsibility for proper professionalism of journalism practice in Nigeria.